2011
DOI: 10.5194/angeo-29-1713-2011
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of the terrestrial field-aligned current system

Abstract: Abstract. We present the first ever comprehensive statistical study of the spatiotemporal characteristics of field-aligned currents in the terrestrial magnetosphere-ionosphere system using multi point measurements. We determine how the FAC density, variability and scale size are coupled. The three ST 5 satellites were in a pearls-on-a-string formation making measurements of the magnetic field with variable interspacecraft separations ranging from a few seconds to about 10 min. More than 4700 sets of satellite … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
109
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 67 publications
(116 citation statements)
references
References 35 publications
7
109
0
Order By: Relevance
“…For example, Gjerloev et al [2011] concluded that large-scale field-aligned currents dominate energy transfer based on statistics of 3 month data from the three ST-5 spacecraft in a string-of-pearls constellation. For example, Gjerloev et al [2011] concluded that large-scale field-aligned currents dominate energy transfer based on statistics of 3 month data from the three ST-5 spacecraft in a string-of-pearls constellation.…”
Section: Example Application: Resolving Spatiotemporal Dynamics Of Comentioning
confidence: 99%
See 3 more Smart Citations
“…For example, Gjerloev et al [2011] concluded that large-scale field-aligned currents dominate energy transfer based on statistics of 3 month data from the three ST-5 spacecraft in a string-of-pearls constellation. For example, Gjerloev et al [2011] concluded that large-scale field-aligned currents dominate energy transfer based on statistics of 3 month data from the three ST-5 spacecraft in a string-of-pearls constellation.…”
Section: Example Application: Resolving Spatiotemporal Dynamics Of Comentioning
confidence: 99%
“…For example, Gjerloev et al [2011] concluded that large-scale field-aligned currents dominate energy transfer based on statistics of 3 month data from the three ST-5 spacecraft in a string-of-pearls constellation. If events such as the one presented are common, analyses such as Gjerloev et al [2011] may be missing an entire regime of large-amplitude signal due to undersampling. Figure 19 (bottom) is smoothed with a 3 s running mean to approximate the effect of averaging at the 3 s spin-rate used in Gjerloev et al [2011].…”
Section: Example Application: Resolving Spatiotemporal Dynamics Of Comentioning
confidence: 99%
See 2 more Smart Citations
“…This is consistent with the equatorward edge of the R1 current and a region in the ionosphere where R1 and R2 close. The FAC system has typical temporal variability scales of 40-60 s on the dayside and~90-140 s on the nightside (Gjerloev et al 2011). Thus, IT modeling based on models of FAC may not be able to capture the short-time and smallscale variability of the Joule heating patterns.…”
Section: Discussionmentioning
confidence: 99%